Ruralidades, Escuela y Comunidades: configuración de deseos en jóvenes de la Escuela "Las Aves" de Colombia - Jennifer Munireh Cortés Moncada; Felipe Navarro Nicoletti; Jimena Isabel Petrona Aguirre (Universidade Federal do Norte do Tocantins, 2021)
Rural youth find themselves in the dilemma -often- of deciding to leave their communities in search of a better future because of different factors (psychosocial, economic, and cultural). This work is based on a research internship that promoted interdisciplinary dialogue in the framework of the rural schools in Argentina and, on the other hand, Colombian educational institutions. In this case, the study focuses on the "Las Aves" School in the community of El Águila, located in the North of Colombia's Cauca. The methodology used was qualitative with a community psychosocial approach, and the video-documentary technique was used for the analysis of discursive narrative content. In addition, narrative interviews were conducted with key referents such as educational leaders, school rector, and young people in the seventh year of secondary school. The proposed analysis (from the educational perspective, community psychology and communication) strengthened research processes that solidify contributions -especially- from the voices and desires of young people for the visibility of the conversation of the right to conditions of progress and social inclusion.